Pengaruh Minat Dan Motivasi Terhadap Pemahaman Matematika Siswa Kelas X SMA Negeri 1 Dolok Batu Nanggar - Sinambela, Debora; KMA Fauzi; Kartono (JURNAL MATHEMATIC PAEDAGOGIC, 2026)
This study examines the effects of learning interest (X1) and learning motivation (X2) on students’ mathematical understanding ability (Y) among Grade 10 students at SMA Negeri 1 Dolok Batu Nanggar in the 2024/2025 academic year. A quantitative approach was employed with a sample of 52 students selected through proportional random sampling. Data on interest and motivation were collected using questionnaires, while mathematical understanding was measured using an essay-type test. Data were analyzed using multiple linear regression with SPSS 21, preceded by assumption testing. The Kolmogorov–Smirnov test indicated that all variables were normally distributed (interest Sig. = .207; motivation Sig. = .517; understanding Sig. = .358; all > .05). Regression results showed that interest had a positive and significant effect on mathematical understanding (β = .799, t = 9.397, p < .001), and motivation also had a positive and significant effect (β = .601, t = 5.320, p < .001). Simultaneously, interest and motivation significantly predicted mathematical understanding (F = 60.156, p < .001) with R² = .711, indicating that 71.1% of the variance in mathematical understanding was explained by the two predictors. In the multiple regression model, interest was the more dominant predictor compared to motivation (βinterest = .663 > βmotivation = .301). These findings highlight the importance of strengthening students’ learning interest and motivation to improve mathematical understanding.